2017
DOI: 10.1039/c7cp00195a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high energy electron irradiation on the network structure of gelatin hydrogels as investigated by small-angle X-ray scattering (SAXS)

Abstract: The impact of high energy crosslinking on the network structure of gelatin hydrogels was investigated in comparison to physically entangled gels by small-angle X-ray scattering (SAXS). Physically entangled gelatin of increasing concentration exhibited a nearly constant correlation length of several nanometers. These gels had scattering behavior close to that of polymer coils swollen in a good solvent, as evidenced by the Porod exponent of 1.8. The mass fractal dimension decreased towards 1, indicating increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Such feature indicates that the network structures can be described by a combination of polymer concentration fluctuations at the high q region and density differences of static inhomogeneities at the low q region, which are represented by the Lorentzin-type function and the Debye-Bueche function, respectively 29 . However, we found that a large uncertainty was associated with estimating the characteristic length of inhomogeneities because we only observed a constant slope of -4 at a low q region, indicating that the characteristic length of inhomogeneities was too large to be probed by the SAXS analysis 30 . Consequently, we employed a combined equation of the approximated Debye-Bueche function and the Lorentzian type function to predict the scattering intensity I(q)…”
mentioning
confidence: 73%
“…Such feature indicates that the network structures can be described by a combination of polymer concentration fluctuations at the high q region and density differences of static inhomogeneities at the low q region, which are represented by the Lorentzin-type function and the Debye-Bueche function, respectively 29 . However, we found that a large uncertainty was associated with estimating the characteristic length of inhomogeneities because we only observed a constant slope of -4 at a low q region, indicating that the characteristic length of inhomogeneities was too large to be probed by the SAXS analysis 30 . Consequently, we employed a combined equation of the approximated Debye-Bueche function and the Lorentzian type function to predict the scattering intensity I(q)…”
mentioning
confidence: 73%
“…It indicates there is mass fractal and the ion-rich domains are dispersed as interconnected (branched) networks, confirming the formation of ion channels in our material 25 . Besides, the scattering shoulder at low scattering vectors, as indicated by an arrow, suggests long-range order of the ion channels 26 . The mesh size of these channels is estimated as , i.e., about 10-nm diameter.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there were electron density differences between the soft and hard segments in the SMPU matrix as well as between the SMPU matrix and SiO 2 particles in the SiO 2 /SMPU, which led to electron density fluctuations at the above interfaces. The interphase interaction between molecular chains of the SMPU matrix and SiO 2 particles is the main cause of a positive deviation [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there were electron density differences between the soft and hard segments in the SMPU matrix as well as between the SMPU matrix and SiO 2 particles in the SiO 2 /SMPU, which led to electron density fluctuations at the above interfaces. The interphase interaction between molecular chains of the SMPU matrix and SiO 2 particles is the main cause of a positive deviation[37].On one hand, there are many formed defects at the interfaces between the hard and soft segments as well as between the SMPU matrix and SiO 2 particles. The defects between them further result in the generation of space charges, which affects the electron density[38].…”
mentioning
confidence: 99%